Experimental evaluation of thermal properties of R134a clathrates based PCMs for cooling applications - Zafar, Sayem; Dincer, Ibrahim; Gadalla, Mohamed (ELSEVIER SCI LTD, 2016)
The thermal properties of R134a clathrates with additives, which are treated as phase change materials (PCMs), are experimentally determined. The formation of refrigerant clathrates is investigated due to their potential use in active as well as in passive cooling applications. The PCMs are formed using R134a clathrate and distilled water with different refrigerant proportions and five different additives. The main objective of using additives is to study their potential for enhancing the clathrate thermal properties under direct contact heat transfer. PCMs are formed in glass tubes and their temperatures are recorded, at two different locations inside the tube, after regular intervals. The R134a percentages of 35% are used to form clathrate. For the additives, ethanol, sodium chloride, magnesium nitrate hexahydrate, copper and aluminum are used. PCMs are formed using a controllable constant energy water bath. The thermal properties determined are the liquid phase thermal conductivity, mushy phase thermal conductivity, and specific latent heat of the PCMs. A comparative study is conducted to compare the thermal properties of different PCMs using the suggested additives. The copper additive improves the thermal conductivity the most while sodium chloride reduces the thermal conductivity. Ethanol additive improves the specific latent heat the most while magnesium nitrate hexahydrate reduced the specific latent heat. (C) 2016 Elsevier Ltd and IIR. All rights reserved.
Keywords: R134a clathrate; Cooling; Thermal conductivity; Specific heat; Latent heat; PCM; Additives; PHASE-CHANGE MATERIALS; GAS-HYDRATE; STORAGE PROCESS; HEAT-TRANSFER; CONDUCTIVITY; MODEL; DISSOCIATION; REFRIGERANTS; GLYCOL; Thermodynamics; Engineering